Cybersecurity policies and strategies for cyberwarfare prevention - Richet, Jean-Loup, 1988- (Advances in digital crime, forensics, and cyber terrorism (ADCFCT) book series., 2015)
"This book serves as an integral publication on the latest legal and defensive measures being implemented to protect individuals, as well as organizations, from cyber threats by examining online criminal networks and threats in both the public and private spheres"--